2018
DOI: 10.1111/php.13016
|View full text |Cite
|
Sign up to set email alerts
|

Size‐dependent Tumor Response to Photodynamic Therapy and Irinotecan Monotherapies Revealed by Longitudinal Ultrasound Monitoring in an Orthotopic Pancreatic Cancer Model

Abstract: Longitudinal monitoring of tumor size in vivo can provide important biological information about disease progression and treatment efficacy that is not captured by other modes of quantification. Ultrasound enables high-throughput evaluation of orthotopic mouse models via fast acquisition of three-dimensional tumor images and calculation of volume with a reasonable degree of accuracy. Herein, we compare orthotopic pancreatic tumor volume measurements determined by ultrasound with volume measured by calipers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…For example, in preclinical setting, accuracy of US‐based volumetric measurements has been demonstrated by Pigula et al ., where they measured orthotopic pancreatic tumor volume with US imaging and found strong correlations with the gold standard of tumor weight and caliper‐derived volume measurements of excised tumors (Fig. ) . Furthermore, the study also revealed a tumor size‐dependent response to PS benzoporphyrin derivative‐based PDT.…”
Section: Role Of Us Imaging In Pdtmentioning
confidence: 74%
“…For example, in preclinical setting, accuracy of US‐based volumetric measurements has been demonstrated by Pigula et al ., where they measured orthotopic pancreatic tumor volume with US imaging and found strong correlations with the gold standard of tumor weight and caliper‐derived volume measurements of excised tumors (Fig. ) . Furthermore, the study also revealed a tumor size‐dependent response to PS benzoporphyrin derivative‐based PDT.…”
Section: Role Of Us Imaging In Pdtmentioning
confidence: 74%
“…Nal‐BPD and Nal‐PpIX were reproducibly synthesized via the freeze‐thaw extrusion method . A lipid composition of dipalmitoylphosphatidylcholine (DPPC), cholesterol and distearoylphosphatidylethanolamine‐methoxy polyethylene glycol (DSPE‐PEG) at a 20:10:1 molar ratio was used based on the clinically approved PEGylated nanoliposomal formulations .…”
Section: Resultsmentioning
confidence: 99%
“…Nanoliposomes containing BPD or PpIX within the bilayer (Nal‐BPD or Nal‐PpIX) were synthesized via freeze‐thaw extrusion as described previously . Briefly, dipalmitoylphosphatidylcholine (DPPC), cholesterol, distearoylphosphatidylethanolamine‐methoxy polyethylene glycol (DSPE‐PEG) and 1,2‐dioleoyl‐3‐trimethylammonium‐propane (DOTAP) (Avanti Polar Lipids, Alabaster, AL, USA) were codissolved with BPD (50 nmoles, U.S. Pharmacopeia, Rockville, MD, USA) at 0.15 mol% BPD‐to‐lipid ratio or PpIX (60 nmoles, Santa Cruz Biotechnology, Dallas, TX, USA) at 0.18 mol% PpIX‐to‐lipid ratio.…”
Section: Methodsmentioning
confidence: 99%
“…There continues to be support for three major PDT research groups (University of Pennsylvania, Massachusetts General Hospital/Harvard and Roswell Park Cancer Center). There are implications for use of PDT in otherwise poorly‐responsive tumors, for example, pancreatic cancer and mesothelioma . At this point, an appreciation for what PDT can do appears to be limited to a few centers in the US.…”
Section: Discussionmentioning
confidence: 99%